Changes in the Response of the Northern Hemisphere Carbon Uptake to Temperature Over the Last Three Decades. Issue 9 (4th May 2018) - Yin, Yi; Ciais, Philippe; Chevallier, Frederic; Li, Wei; Bastos, Ana; Piao, Shilong; Wang, Tao; Liu, Hongyan
Abstract: The CO2 seasonal cycle amplitude (SCA) in the Northern Hemisphere has increased since the 1960s—a feature attributed mainly to enhanced vegetation activity along climate warming and CO2 increase. We identified a temporal change in the sign of the correlation between SCA and air temperature (T) from positive to negative around the year 2000 at most Northern Hemisphere ground stations, consistent with signals from satellite column CO2 measurements since the mid‐2000s. Further, we explored potential causes of this change using net biome productivity estimates from three atmospheric inversions for the period 1980–2015. The change in the SCA‐T relationship is primarily attributable to changes in the net biome productivity‐T relationship: positive correlations weakened in the spring in the high latitudes, confirming a limit to the "warmer spring‐bigger carbon sink" mechanism; negative correlations diminished in the autumn/winter in the mid‐to‐high latitudes, challenging the "warmer winter‐larger carbon release" assumption and highlighting the complexity of carbon processes outside the peak growing season. Plain Language Summary: The seasonal cycle amplitude (SCA) of atmospheric CO2 —an integrated signal of the terrestrial ecosystem metabolism—has increased since the 1960s in the Northern Hemisphere, a feature attributed mainly to enhanced vegetation activity along climate warming and CO2 increase. Earlier studies suggest a strong positive year‐to‐year correlation between SCA and air temperature (T). Here we identified a temporal change in the sign of the SCA‐T correlation from positive to negative around the year 2000 at most Northern Hemisphere ground stations, consistent with signals from satellite column CO2 observations. We further explored potential causes of this change using land carbon flux (termed as net biome productivity) estimates from three atmospheric inversions for the period 1980–2015. The change in the SCA‐T relationship is primarily attributable to changes in the net biome productivity‐T relationship: positive correlations weakened in the spring in the high latitudes, confirming a limit to the "warmer spring‐bigger carbon sink" mechanism; negative correlations diminished in the autumn/winter in the mid‐to‐high latitudes, challenging the "warmer winter‐larger carbon release" assumption. This finding highlights a dynamic temperature sensitivity of the terrestrial ecosystem to climate warming and cautions the use of current carbon‐climate response to constrain future projections. Key Points: The correlation between CO2 seasonal cycle amplitude and temperature became negative around the year 2000 at most northern stations The positive spring net biome productivity‐temperature correlation has been weakening since the mid‐1990s The negative autumn/winter net biome productivity‐temperature correlation has diminished in the mid‐to‐high latitudes since the early‐2000s